Complete mitochondria! genome data and phylogenetic analysis of the Great Marquis, Bassarona dunya (Doubleday, 1848) (Lepidoptera: Nymphalidae: Limenitidinae) from Malaysia - Migaa, Marylin; Yong Zi Yapa, Yong Zi Yapa; Jaharia, Puteri Nur Syahzanani; Parimannan, Sivachandran; Rajandas, Heera; Latifr, Muhammad Abu Bakar; Yap Jing Wei, Yap Jing Wei; Shamsir, Mohd Shahir; Mohd Salleha, Faezah (Taylor&francis, 2023)
The Great Marquis or Bassarona dunya is a butterfly species commonly found in the tropical regions of Asia, America, and Africa. This butterfly is a member of the subfamily Limenitidinae and the classifica-tion within this subfamily has been unstable. Here, we report the first complete mitochondrial genome (mitogenome) of B. danya sampled from Malaysia. The mitogenome is 15,242 by long, comprising a set of 13 protein-coding genes (PCGs), 22 transfer RNAs (tRNAs), two ribosomal RNAs (rRNAs), and an A ±T rich region. All PCGs were initiated by the typical ATN codon, except for COX1 which started with a CGA start codon. Nine PCGs were terminated with a TAA or TAG stop codon, while COX1, COX2, NAD4, and NAD5 ended with an incomplete T. The 12S and 165 rRNAs were 716 by and 1269 by in length, respectively. Phylogenetic analysis supported the placement of B. dunya within Limenitidinae with a high support value.